Assessment of career movements of Philippine High School for the Arts (PHSA) ballet graduates - Villanueva, Ava Maureen B.
This study will serve as an assessment of the career movements of these swans (graduates of the school) who have become an instrument in propagating art in the Philippines either as ballet dancers or ballet teachers. The concentration of the study will then focus on PHSA ballet graduates pursuing a career as ballet teachers. Since the school has produced already numerous ballet graduates who are presently teaching ballet, I chose only those who are teaching ballet in Metro Manila.